Pengembangan Video Animasi Pada Tema Sikap atau Perilaku Yang Menjaga dan Merusak Keutuhan NKRI Pada Siswa Kelas IV SD Negeri 1 Airgegas - Filda Anandita; Vika Martahayu; Fandi Nugroho (JBES (Journal Basic Education Skills), 2025)
This research was inspired by the limited learning resources available for students to use in the classroom, resulting from the suboptimal use of learning media. Current teaching methods do not utilize digital learning resources; instead, the curriculum is based on static visuals and textbooks. The primary objective of this research is to provide a credible, practical, and productive learning tool for fourth-grade students at SD Negeri 1 Airgegas in the form of an animated film. Using the ADDIE development methodology, which stands for Analysis, Design, Development, Implementation, and Evaluation, this research involved an R&D approach. One educator and twenty-two fourth-grade students from SD Negeri 1 Airgegas participated in the study. Interviews, questionnaires, and documentation served as data collection instruments. The data analysis process included evaluating hypotheses, reliability, normality, and validity of the instruments used. Data on effectiveness were collected through pre- and post-test score studies, while data on feasibility were drawn from interviews and questionnaires. A small-group experiment achieved 96.6% success rate, a large-group test achieved 95% success rate, and validation findings by media experts achieved 75%. With a t-value of 14.369, the findings showed an increase from 52.5% before the test to 80.2% after. The average post-test score reached 86.36%, an increase from 52.72% before. Ha was approved, indicating a significant change before and after watching the animated video material, according to the paired sample t-test findings (33.745 > 1.721). Finally, the animated film entitled "Attitudes and Behaviors that Maintain and Disrupt the Unitary State of the Republic of Indonesia (NKRI)" was considered a practical and efficient learning tool.